Consolation Strategies in Children's Television News: A Longitudinal Content Analysis. (26th November 2022) - Kleemans, Mariska; Tamboer, Sanne L.
ABSTRACT: Engaging children in news is important for their participation in the public sphere. However, producers of children's news face a trade-off between fully informing children and not causing distress. Against the background of technological, economic, and ideological changes in the media landscape, this study examined the use of consolation strategies in the Dutch children's news, and whether these have shifted between 2000 and 2016. A manual content analysis was conducted, focusing on strategies used within the entire newscast ( N = 408 programs), within items ( N = 2, 304 items), and within camera shots ( N = 41, 338 shots). Results showed that, on the one hand, the Dutch children's news seems to become less inclined to protect children, by showing a decrease in expert sources and distant shots, and an increase in the repetition of sensational images and the prevalence of frightening sounds. On the other hand, the attention for sensational topics is relatively low and has not changed over time. Also, the use of the sandwich formula, animations and reassuring comments by the host or reporter did not change over the years. Yet, the use of children as a source has risen, which might signal a greater focus on stories of children themselves.